(untitled) (Journal of Applied Oral Science, 2021)
Objective: This study analyzed the effect of ionizing radiation on bone microarchitecture and biomechanical properties in the bone tissue surrounding a dental implant. Methodology: Twenty rabbits received three dental morse taper junction implants: one in the left tibia and two in the right tibia. The animals were randomized into two groups: the nonirradiated group (control group) and the irradiated group, which received 30 Gy in a single dose 2 weeks after the implant procedure. Four weeks after the implant procedure, the animals were sacrificed, and the implant/bone specimens were used for each experiment. The specimens (n=10) of the right tibia were examined by microcomputed tomography to measure the cortical volume (CtV, mm3), cortical thickness (CtTh, mm) and porosity (CtPo, %). The other specimens (n=10) were examined by dynamic indentation to measure the elastic modulus (E, GPa) and Vickers hardness (VHN, N/mm2) in the bone. The specimens of the left tibia (n=10) were subjected to pull-out tests to calculate the failure load (N), displacement (mm) up to the failure point and interface stiffness (N/mm). In the irradiated group, two measurements were performed: close, at 1 mm surrounding the implant surface, and distant, at 2.5 mm from the external limit of the first measurement. Data were analyzed using one-way ANOVA, Tukey’s test and Student’s t-test (α=0.05). Results: The irradiated bone closer to the implant surface had lower elastic modulus (E), Vickers hardness (VHN), Ct.Th, and Ct.V values and a higher Ct.Po value than the bone distant to the implant (P<0.04). The irradiated bone that was distant from the implant surface had lower E, VHN, and Ct.Th values and a higher Ct.Po value than the nonirradiated bone (P<0.04). The nonirradiated bone had higher failure loads, displacements and stiffness values than the irradiated bone (P<0.02). Conclusion: Ionizing radiation in dental implants resulted in negative effects on the microarchitecture and biomechanical properties of bone tissue, mainly near the surface of the implant.